ANTIDIABETIC ACTIVITY OF KOVAI KIZHANGU CHOORANAM IN ALLOXAN INDUCED DIABETIC RATS: Pharmaceutical Science-Pharmacology - P. PARTHIBAN; RAVIKUMAR; J. ANBU; ANJANA, ASHWINI (International Journal of Life Science and Pharma Research, 2012)
Kovai Kizhangu Choornam has been widely used in Siddha system of medicine for diabetes. The powder (Kovai Kizhangu Choornam) showed a significant inhibitory effect was screened at 500 mg/kg, for the in vivo anti-diabetic activity on alloxan induced diabetic rats. Glibenclamide: Metformin (0.5:40mg/kg) used as reference standard. Single dose (400 mg/kg) treatment with the siddha drug Kovai Kizhangu Choornam produced anti-hyperglycaemic effect (antidiabetic effect). The trial drug showed a significant anti-diabetic activity and were comparable with that of standard thus validating the traditional claim of the plan